Sulfur dioxide resistance in Saccharomyces cerevisiae: beyond SSU1 - Estéfani García-Ríos; José Manuel Guillamón (Microbial Cell)
Sulfite resistance is an important oenological trait for wine yeasts because this compound is used during winemaking as a microbial inhibitor and antioxidant. The molecular mechanisms by which Saccharomyces cerevisiae responds and tolerates SO2 have been mainly focused on the sulfite efflux pump encoded by SSU1. Different chromosomal rearrangements in the regulatory region of this gene have been correlated with improved sulfite tolerance. However, other molecular factors must contribute to this trait because the SSU1 gene activity does not always fit with sulfite tolerance. An interesting approach to shed light onto this issue could be found by Lage et al. (2019). These authors have combined transcriptomic and genome-wide analysis to describe how the poorly characterized transcription factor Com2 controls, directly or indirectly, the expression of more than 80% of the genes activated by SO2. Additionally, large-scale phenotyping revealed the identification of 50 Com2-targets contributing to the protection against SO2. This information is very interesting for gaining knowledge regarding this important industrial trait.